A fuzzy logic-based sustainable and trusted routing for P2P enabled smart grid. (2016) - Xiang, Ming; Liu, William; Bai, Quan
Smart grid is the trend of next generation electrical power system which has integrated the information and communication technologies and enables the existing power grid to perform more intelligent and efficient operations. A high level of network availability is therefore required to guarantee two-way flows of electricity and information among electrical units. The peer-to-peer wireless mesh network infrastructure can provide redundant routes for the smart grid communications to ensure the network availability. However, the P2P infrastructure is vulnerable to cyber-attacks. In this paper, we propose a new fuzzy-based energy aware trusted geo-routing (FEATGR), which can decide the optimal end-to-end path between any source and destination by effectively leveraging the energy consumption, location and trust metrics. The extensive simulation studies have confirmed that FEATGR is capable to achieve the stable and secured routing performance and also can guarantee the high level of network availability for P2P smart grid communications.